Improved blasting results with precise initiation : Numerical simulation of sublevel caving blasting - Yi, Changping (Luleå tekniska universitet, Geoteknologi, 2013)
A series of numerical simulations of rock blasting using LS-DYNA software havebeen conducted to investigate the effect of short delay time on the fragmentation inunderground mines. The purpose was to test the hypothesis proposed by Rossmaniththat stress wave interaction could result in finer fragmentation by controlling theinitiation times. The blasted rock was simulated with RHT material model. After thecalculation, the elements with damage level above 0.6 were removed to simulate thefracture of the rock.The size of model and the borehole pattern were based on the blasting design of theLKAB Malmberget mine. Several simulations were run to investigate the effects ofinitiation time, primer position and boundary conditions. The results are presented asaccumulated area plots where the level of fragmentation can be observed at certainpositions in the model.The results show that the fragmentation for simultaneous initiation is coarsercompared to initiation with delay times in SLC blasting. It is difficult to identify anyeffect of stress wave interaction from the damage distribution in the blasted blockbecause the borehole pattern is in a fan shape. Thus, the distance between twoadjacent boreholes is not constant and the boreholes are of various lengths. Thenumerical modeling results showed that the fragmentation for the case of 2 ms delaytime is finer than that of simultaneous initiation and the 1 ms delay time case. Thecomparison among the cases with different primer positions shows that if the top ofthe block was set as free face, the bottom primer cases yielded the finer fragmentationthan the top primers cases and the middle primer cases; if the top of the block was setas non-reflecting boundary, the top primer cases yielded the finest fragmentation. Theeffect of overlying waste rock above the block cannot be neglected in simulations.The real boundary conditions of the top of the block and the effect of primer positionneed to be studied further. Some recommendations are proposed for the futureresearch about SLC ...